Electrolyte, battery and electric equipment

By using a combination of electrolyte sodium salt, dispersant, wetting agent and electrolyte membrane stabilizer in the electrolyte solution, the problem of the electrolyte membrane of sodium ion battery is easily dissolved at high temperatures, and the high-temperature cycle stability, first effect and capacity of the battery are improved.

CN119833750APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410797102.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The electrolyte membrane of existing sodium ion batteries is easily dissolved at high temperatures, resulting in interface gas production, increased impedance and attenuation of battery capacity.

Method used

An electrolyte solution containing an electrolyte sodium salt, a dispersant, a wetting agent and an electrolyte membrane stabilizer is adopted. The electrolyte membrane stabilizer includes an alkali metal halide, a sodium compound and an aluminum compound. Through the action of the dispersant and the wetting agent, the electrolyte membrane stabilizer is evenly dispersed to inhibit the dissolution of the electrolyte membrane.

Benefits of technology

Effectively inhibit the dissolution of the electrolyte membrane and improve the high-temperature cycle stability, first-time efficiency and capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833750A_ABST
    Figure CN119833750A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte, a battery and electric equipment, the electrolyte comprises an electrolyte sodium salt, an additive and an organic solvent, the additive comprises a dispersant, a wetting agent and an electrolyte membrane stabilizer, and the electrolyte membrane stabilizer comprises at least one of an alkali metal halide, a sodium compound and an aluminum compound. The electrolyte provided by the invention can inhibit the dissolution of an electrolyte membrane, improves the first efficiency and capacity of the battery, and is beneficial to improving the high-temperature cycling stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to electrolytes, batteries and electrical equipment. Background Art

[0002] At present, the electrolyte needs to form an electrolyte film with good stability on the surface of the positive electrode and the negative electrode to improve the high-temperature cycle stability of the battery. The electrolyte membrane of the sodium-ion battery includes inorganic sodium compounds and organic sodium compounds, which have high solubility and are easily dissolved at high temperatures. They need to be constantly repaired, resulting in interfacial gas production, increased impedance, and battery capacity decay. In the related technology, the dissolution of the electrolyte membrane can be alleviated by introducing low-polarization fluorine-containing solvents or using positive and negative electrode materials with low-solubility coatings. However, low-polarization fluorine-containing solvents have high costs and poor economic benefits, and the coating layer of the negative electrode material has low uniformity and poor electrochemical performance, which are not conducive to improving the first-cycle coulomb efficiency and capacity of the battery. Therefore, there is a need for an electrolyte that can inhibit the dissolution of the electrolyte membrane and improve the first efficiency, high-temperature cycle stability and capacity of the battery. Summary of the invention

[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device. The electrolyte includes an electrolyte membrane stabilizer, a dispersant and a wetting agent, which can inhibit the dissolution of the electrolyte membrane and is beneficial to improving the initial efficiency, high-temperature cycle stability and battery capacity of the battery.

[0004] In a first aspect, the present application provides an electrolyte, which includes an electrolyte sodium salt, an additive and an organic solvent; the additive includes a dispersant, a wetting agent and an electrolyte membrane stabilizer, and the electrolyte membrane stabilizer includes at least one of an alkali metal halide, a sodium compound, and an aluminum compound.

[0005] Optionally, the alkali metal halide includes at least one of NaF, NaCl, NaBr, KF, KCl and KBr, the aluminum compound includes at least one of Al2O3, Al(OH)3 and AlF3, and the sodium compound includes Na3PO4, Na4P2O7, (NaPO3)2, NaPO3 and Na5P3O 10 , at least one of NaAlO2, Na2SO4, NaAlF4, Na2C2O4, NaNO3 and NaNO2.

[0006] Optionally, the electrolyte membrane stabilizer includes at least one of NaF, KF, NaBr, Na2C2O4, Na3PO4, NaAlO2, Al2O3, AlF3, NaNO3 and Na2SO4.

[0007] Optionally, the electrolyte membrane stabilizer includes at least one of Al2O3, NaNO3, AlF3 and Na2C2O4.

[0008] Optionally, the Dv50 particle size of the electrolyte membrane stabilizer is less than or equal to 200 nm.

[0009] Optionally, based on the mass of the electrolyte, the mass percentage of the electrolyte membrane stabilizer is 0.5%-5%; the mass percentage of the dispersant is 0.1%-2%; the mass percentage of the wetting agent is 0.05%-1%; the mass percentage of the electrolyte sodium salt is 7.43%-14.9%; and the mass percentage of the organic solvent is 74.32%-91.4%.

[0010] Optionally, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol and sodium polystyrene sulfonate.

[0011] Optionally, the wetting agent includes at least one of diallyldimethylammonium chloride, sodium dodecylbenzenesulfonate and hexadecyltrimethylammonium bromide.

[0012] Optionally, the electrolyte sodium salt includes at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisoxalatoborate, sodium difluorophosphate, sodium difluorooxalatoborate, sodium difluorobisoxalatophosphate and sodium bisfluorosulfonyl imide.

[0013] Optionally, the organic solvent includes at least one selected from cyclic carbonates, linear carbonates, propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, ethyl propionate and methyl butyrate.

[0014] Optionally, the additives also include conventional additives, which include at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, propenyl-1,3-sultone, methylene disulfonate, vinyl sulfate, trimethylsilyl phosphate, trimethylsilyl phosphite, trimethylsilyl borate, succinonitrile, 1,3,6-hexanetrinitrile and adiponitrile.

[0015] Optionally, the mass percentage of the conventional additive is 0.093%-4.97%.

[0016] Optionally, the electrolyte is in the form of a colored emulsion.

[0017] The electrolyte provided in the present application includes electrolyte sodium salt, electrolyte membrane stabilizer, dispersant and wetting agent. The dispersant and wetting agent promote the uniform dispersion of the electrolyte membrane stabilizer, which can inhibit the dissolution of the electrolyte membrane, improve the high-temperature cycle stability of the battery, and enhance the initial efficiency and capacity of the battery.

[0018] In a second aspect, the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and an electrolyte disposed between the positive electrode sheet and the negative electrode sheet, wherein the electrolyte comprises the electrolyte described in the first aspect.

[0019] The battery provided in this application has high capacity, good high-temperature cycle stability and excellent initial efficiency.

[0020] In a third aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the second aspect.

[0021] The electrical equipment provided by this application has high safety performance, long service life and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0023] Figure 1 A schematic diagram of a cross-sectional structure of a battery provided in one embodiment of the present application;

[0024] Figure 2 A schematic diagram of the cross-sectional structure of a battery provided in another embodiment of the present application. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] The present application provides an electrolyte, which includes electrolyte sodium salt, additives and organic solvents. The additives include dispersants, wetting agents and electrolyte membrane stabilizers. The electrolyte membrane stabilizer includes at least one of alkali metal halides, sodium compounds and aluminum compounds. In the present application, the electrolyte sodium salt can improve the conductivity of the electrolyte, improve the ionic conductivity and electronic conductivity; the dispersant can improve the solubility of the electrolyte membrane stabilizer, avoid the agglomeration of the electrolyte membrane stabilizer in the electrolyte, and promote the uniform dispersion of the electrolyte membrane stabilizer in the electrolyte; the wetting agent can reduce the surface energy of the electrolyte membrane stabilizer, improve the dispersibility of the electrolyte membrane stabilizer in the electrolyte, and improve the contact ability between the electrolyte and the electrode plate; the electrolyte membrane stabilizer is uniformly dispersed in the electrolyte under the joint action of the dispersant and the wetting agent, and can be deposited on the surface of the electrode plate. During the use of the battery, it can be slowly released to inhibit the dissolution of the components in the electrolyte membrane and improve the capacity and high-temperature cycle stability of the battery; at the same time, the electrolyte membrane stabilizer deposited on the surface of the electrode plate can play the role of the electrolyte membrane, improve the ion transmission capacity, and help to improve the capacity, first effect and high-temperature cycle stability of the battery. The electrolyte provided in the present application can inhibit the dissolution of the electrolyte membrane, improve the high-temperature cycle stability of the battery, and help to improve the capacity and first effect of the battery.

[0027] In the present application, the dispersant is a class of organic polymers with surface active groups, which have a hydrophilic effect and can be wrapped on the surface of the electrolyte membrane stabilizer that is insoluble in the electrolyte, thereby promoting the dissolution of the electrolyte membrane stabilizer in the electrolyte; at the same time, the groups on the surface of the dispersant are charged, and like-charge repulsion occurs between the electrolyte membrane stabilizers, which is beneficial to the uniform dispersion of the electrolyte membrane stabilizer in the electrolyte, avoiding the agglomeration and aggregation of the electrolyte membrane stabilizer, and the occurrence of stratification, making the electrolyte in an emulsion state.

[0028] In one embodiment of the present application, the dispersant can promote the dispersion of the electrolyte membrane stabilizer. Specifically, the dispersant can include but is not limited to at least one of polyvinyl pyrrolidone, polyethylene glycol and sodium polystyrene sulfonate. In one embodiment of the present application, the dispersant can be polyvinyl pyrrolidone. In another embodiment of the present application, the dispersant can be polyethylene glycol.

[0029] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the dispersant is 0.1%-2%. An appropriate amount of dispersant can improve the stability of the electrolyte, which is beneficial to improving the capacity and high-temperature cycle stability of the battery. Specifically, in the electrolyte, the mass percentage of the dispersant can be, but is not limited to, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.85% or 2%, etc. In one embodiment of the present application, in the electrolyte, the mass percentage of the dispersant can be 0.1%-1.5%. In another embodiment of the present application, in the electrolyte, the mass percentage of the dispersant can be 1%-2%.

[0030] In the present application, the wetting agent is a compound that is both hydrophilic and lipophilic, and contains a hydrophilic group and a lipophilic group. The hydrophilic group is connected to the dispersant that encapsulates the electrolyte membrane stabilizer, and the lipophilic group is easily connected to the electrolyte, which is conducive to the uniform dispersion of the electrolyte membrane stabilizer in the electrolyte, while reducing the surface energy of the electrolyte membrane stabilizer, and further improving the dispersibility of the electrolyte membrane stabilizer in the electrolyte. Specifically, the wetting agent may include, but is not limited to, at least one of diallyldimethylammonium chloride, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide. In one embodiment of the present application, the wetting agent may be sodium dodecylbenzene sulfonate. In another embodiment of the present application, the wetting agent may be hexadecyltrimethylammonium bromide.

[0031] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the wetting agent is 0.05%-1%, and an appropriate amount of wetting agent can improve the dispersion of the electrolyte membrane stabilizer in the electrolyte. Specifically, in the electrolyte, the mass percentage of the wetting agent can be, but is not limited to, 0.05%, 0.06%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%, etc. In one embodiment of the present application, in the electrolyte, the mass percentage of the wetting agent can be 0.05%-0.6%. In another embodiment of the present application, in the electrolyte, the mass percentage of the wetting agent can be 0.5%-1%.

[0032] In the present application, the electrolyte membrane stabilizer is used to generate electrolyte membrane components in situ on the surface of the electrode plate during the charge and discharge process, improve the structural stability of the electrolyte membrane, increase the saturation of the electrolyte membrane components in the electrolyte, inhibit the dissolution of the electrolyte membrane, enhance the ionic conductivity of the electrolyte membrane, and help improve the thermal stability of the battery. Specifically, the electrolyte membrane stabilizer may include but is not limited to at least one of alkali metal halides, sodium compounds, and aluminum compounds; illustratively, the alkali metal halide may include but is not limited to at least one of NaF, NaCl, NaBr, KF, KCl, and KBr, the aluminum compound may include but is not limited to at least one of Al2O3, Al(OH)3, and AlF3, and the sodium compound may include but is not limited to Na3PO4, Na4P2O7, (NaPO3)2, NaPO3, Na5P3O 10 , NaAlO2, Na2SO4, NaAlF4, Na2C2O4, NaNO3 and NaNO2. In one embodiment of the present application, the electrolyte membrane stabilizer may be NaF, which may further inhibit the dissolution of the electrolyte membrane, increase the sodium ion content in the electrolyte, and improve the high temperature stability and capacity of the battery. In another embodiment of the present application, the electrolyte membrane stabilizer may include NaF and Na4P2O7.

[0033] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the electrolyte membrane stabilizer is 0.5%-5%. An appropriate amount of electrolyte membrane stabilizer can improve the capacity and high temperature cycle stability of the battery. Specifically, in the electrolyte, the mass percentage of the electrolyte membrane stabilizer can be, but is not limited to, 0.5%, 1%, 2%, 3%, 4% or 5%. In one embodiment of the present application, in the electrolyte, the mass percentage of the electrolyte membrane stabilizer can be 0.5%-3%. In another embodiment of the present application, in the electrolyte, the mass percentage of the electrolyte membrane stabilizer can be 2.5%-5%.

[0034] In one embodiment of the present application, the Dv50 particle size of the electrolyte membrane stabilizer is less than or equal to 200nm, and the Dv50 particle size is the corresponding particle size when the volume cumulative distribution in the system accounts for 50%. The nano-level electrolyte membrane stabilizer has good dispersion performance, is not easy to settle and stratify, and improves the dispersion of the electrolyte; the nano-level electrolyte membrane stabilizer can enter the pores of the electrode plate, contact with the active material, and form a thin and uniform deposition layer on the surface of the active material, thereby improving the first efficiency and high-temperature interface stability of the battery and reducing the battery impedance. Specifically, the Dv50 particle size of the electrolyte membrane stabilizer may be, but is not limited to, less than or equal to 200nm, less than or equal to 180nm, less than or equal to 160nm, less than or equal to 150nm, or less than or equal to 100nm. In one embodiment of the present application, the Dv50 particle size of the electrolyte membrane stabilizer may be less than or equal to 160nm. In another embodiment of the present application, the Dv50 particle size of the electrolyte membrane stabilizer may be less than or equal to 120nm.

[0035] In one embodiment of the present application, the electrolyte includes an electrolyte sodium salt, which can form an electrolyte film on the surface of the electrode plate to improve the high temperature cycle stability of the battery; the electrolyte sodium salt can improve the conductivity of the electrolyte and improve the ionic conductivity and electronic conductivity. Specifically, the electrolyte sodium salt may include but is not limited to at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate trifluoromethylsulfonate, sodium bistrifluoromethylsulfonyl imide, sodium bisoxalate borate, sodium difluorophosphate, sodium difluorooxalate borate, sodium difluorobisoxalate phosphate and sodium bisfluorosulfonyl imide. In one embodiment of the present application, the electrolyte sodium salt may be sodium hexafluorophosphate. In another embodiment of the present application, the electrolyte sodium salt may be sodium bistrifluoromethylsulfonyl imide and sodium bisfluorosulfonyl imide.

[0036] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the electrolyte sodium salt is 7.43%-14.9%, and an appropriate amount of electrolyte sodium salt is beneficial to improving the high temperature cycle stability of the battery. Specifically, in the electrolyte, the mass percentage of the electrolyte sodium salt may be, but is not limited to, 7.43%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 14.9%, etc. In one embodiment of the present application, in the electrolyte, the mass percentage of the electrolyte sodium salt may be 7.43%-12%. In another embodiment of the present application, in the electrolyte, the mass percentage of the electrolyte sodium salt may be 11%-14.9%.

[0037] In one embodiment of the present application, the organic solvent can promote the uniform dispersion of components, improve the uniformity of the electrolyte, and help improve the electrochemical performance and high temperature cycle stability of the battery. Specifically, the organic solvent can include but is not limited to at least one of cyclic carbonates, linear carbonates, propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, ethyl propionate and methyl butyrate. In one embodiment of the present application, the organic solvent can be diethyl carbonate. In another embodiment of the present application, the organic solvent can be cyclic carbonates and linear carbonates.

[0038] In one embodiment of the present application, the mass percentage of the organic solvent is 74.32%-91.4% based on the mass of the electrolyte. An appropriate amount of organic solvent can promote the dispersion of components. Specifically, in the non-aqueous solution, the mass percentage of the organic solvent can be, but is not limited to, 74.32%, 75%, 80%, 85%, 88%, 90% or 91.4%. In one embodiment of the present application, the mass percentage of the organic solvent in the electrolyte can be 74.32%-88%. In another embodiment of the present application, the mass percentage of the organic solvent in the electrolyte can be 87%-91.4%.

[0039] In one embodiment of the present application, the additive also includes a conventional additive. Specifically, the conventional additive may include but is not limited to vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, propenyl-1,3-sultone, methylene disulfonate, vinyl sulfate, trimethylsilyl phosphate, trimethylsilyl phosphite, trimethylsilyl borate, succinonitrile, 1,3,6-hexane trinitrile and at least one of adiponitrile. In one embodiment of the present application, the conventional additive may be propenyl-1,3-sultone. In another embodiment of the present application, the conventional additive may be adiponitrile.

[0040] In one embodiment of the present application, the mass percentage of conventional additives is 0.093%-4.97% based on the mass of the electrolyte. Specifically, the mass percentage of conventional additives in the electrolyte may be, but is not limited to, 0.093%, 0.1%, 1%, 2%, 3%, 4% or 4.97%. In one embodiment of the present application, the mass percentage of conventional additives in the electrolyte may be 0.093%-3%. In another embodiment of the present application, the mass percentage of conventional additives in the electrolyte may be 2.5%-4.97%.

[0041] In one embodiment of the present application, the electrolyte is in a colored emulsion state, and the color of the electrolyte is different depending on the added dispersant, wetting agent and electrolyte membrane stabilizer; when the dispersant, wetting agent and electrolyte membrane stabilizer are uniformly dispersed in the electrolyte, the electrolyte will not be stratified and form an emulsion state. In one embodiment of the present application, the electrolyte is in a white emulsion state.

[0042] The present application provides a method for preparing an electrolyte, comprising mixing an electrolyte sodium salt, a dispersant, a wetting agent and an electrolyte membrane stabilizer to obtain an electrolyte. The preparation method provided by the present application is simple, does not require an additional preparation process, has a low preparation cost, and the prepared electrolyte can inhibit the dissolution of the electrolyte membrane, improve the capacity, high temperature cycle stability and first efficiency of the battery. The electrolyte provided in any of the above embodiments can be prepared by the preparation method.

[0043] In one embodiment of the present application, the mixing is performed under an inert atmosphere to prevent the occurrence of side reactions. Specifically, the inert gas may be, but is not limited to, at least one of argon, nitrogen, helium, and neon. In one embodiment of the present application, the inert gas may be argon. In another embodiment of the present application, the inert gas may be nitrogen.

[0044] In one embodiment of the present application, in an inert atmosphere, the mass content of water is less than 1ppm, and the mass content of oxygen is less than 1ppm, which reduces the probability of side reactions and improves the purity of the electrolyte. Specifically, the mass content of water may be, but is not limited to, less than or equal to 1ppm, less than or equal to 0.9ppm, less than or equal to 0.8ppm, less than or equal to 0.5ppm, or less than or equal to 0.4ppm, etc.; the mass content of oxygen may be, but is not limited to, less than or equal to 1ppm, less than or equal to 0.9ppm, less than or equal to 0.8ppm, less than or equal to 0.5ppm, or less than or equal to 0.4ppm, etc. In one embodiment of the present application, the mass content of water may be less than 0.8ppm, and the mass content of oxygen may be less than 0.7ppm. In one embodiment of the present application, the mass content of water may be less than 0.5ppm, and the mass content of oxygen may be less than 0.5ppm.

[0045] In one embodiment of the present application, before adding the electrolyte membrane stabilizer, the electrolyte membrane stabilizer is ground to a Dv50 particle size of less than or equal to 200nm by ball milling or the like, and then dried. The drying temperature is greater than or equal to 200°C, which is beneficial to improving the dispersion of the electrolyte membrane stabilizer. Specifically, the drying temperature may be, but is not limited to, greater than or equal to 200°C, greater than or equal to 210°C, greater than or equal to 220°C, greater than or equal to 230°C, greater than or equal to 240°C, or greater than or equal to 250°C. In one embodiment of the present application, the electrolyte membrane stabilizer is ground and then dried at 220°C.

[0046] In one embodiment of the present application, mechanical dispersion is further included after mixing, and the time of mechanical dispersion is greater than or equal to 30 minutes, which can improve the dispersion degree of each component in the electrolyte, inhibit the dissolution of the electrolyte membrane, and improve the capacity and high temperature cycle stability of the battery. Specifically, the time of mechanical dispersion can be, but is not limited to, greater than or equal to 30 minutes, greater than or equal to 40 minutes, greater than or equal to 50 minutes, greater than or equal to 60 minutes, or greater than or equal to 80 minutes. In one embodiment of the present application, the time of mechanical dispersion can be greater than or equal to 40 minutes. In another embodiment of the present application, the time of mechanical dispersion can be greater than or equal to 55 minutes.

[0047] In one embodiment of the present application, after the organic solvent, electrolyte sodium salt and conventional additives are mixed for the first time, a dispersant and a wetting agent are added for the second mixing. After the second mixing, an electrolyte membrane stabilizer is added for the third mixing, followed by mechanical dispersion to obtain an electrolyte.

[0048] In one embodiment of the present application, the first mixing time is 30min-90min, which can promote the solvent dispersion of the organic solvent and the electrolyte salt. Specifically, the first mixing time can be but not limited to 30min, 40min, 50min, 60min, 80min or 90min, etc. In one embodiment of the present application, the first mixing time can be 30min-70min. In another embodiment of the present application, the first mixing time can be 50min-90min.

[0049] In one embodiment of the present application, the second mixing time is greater than or equal to 30 minutes to promote the dissolution of the dispersant and the wetting agent. Specifically, the second mixing time may be, but is not limited to, greater than or equal to 30 minutes, greater than or equal to 40 minutes, greater than or equal to 50 minutes, greater than or equal to 60 minutes, or greater than or equal to 80 minutes. In one embodiment of the present application, the second mixing time may be greater than or equal to 40 minutes.

[0050] In one embodiment of the present application, the third mixing time is greater than or equal to 30 minutes, which promotes the dissolution of the dispersant and the wetting agent. Specifically, the third mixing time may be, but is not limited to, greater than or equal to 30 minutes, greater than or equal to 40 minutes, greater than or equal to 50 minutes, greater than or equal to 60 minutes, or greater than or equal to 80 minutes. In one embodiment of the present application, the third mixing time may be greater than or equal to 40 minutes.

[0051] See also Figure 1 , is a schematic diagram of a cross-sectional structure of a battery provided in one embodiment of the present application, wherein the battery 100 comprises a positive electrode sheet 10, a negative electrode sheet 20, and an electrolyte 30 disposed between the positive electrode sheet 10 and the negative electrode sheet 20, wherein the electrolyte is the electrolyte described in any of the above embodiments. Since the electrolyte can inhibit the dissolution of the electrolyte membrane and improve the ionic conductivity of the electrolyte membrane, it is beneficial to improve the capacity, high temperature cycle stability and first efficiency of the battery.

[0052] See also Figure 2 , is a schematic diagram of a cross-sectional structure of a battery provided in another embodiment of the present application, wherein the positive electrode sheet 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on the surface of the positive electrode current collector 11. Specifically, the positive electrode current collector 11 may be, but is not limited to, at least one of copper, aluminum, nickel, and stainless steel. In one embodiment of the present application, the positive electrode current collector 11 may be aluminum foil.

[0053] In one embodiment of the present application, the positive electrode active material layer 12 includes a positive electrode active material, which may include but is not limited to at least one of a layered oxide, Prussian blue, and a polyanionic compound. In one embodiment of the present application, the positive electrode active material may be a layered oxide. In another embodiment of the present application, the positive electrode active material may be a polyanionic compound.

[0054] In one embodiment of the present application, the positive electrode active material layer 12 also includes a positive electrode conductive agent. The positive electrode conductive agent can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the positive electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the positive electrode conductive agent may be graphite. In another embodiment of the present application, the positive electrode conductive agent may be carbon black.

[0055] In one embodiment of the present application, the positive electrode active material layer 12 also includes a positive electrode binder, which can improve the binding ability of the components in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the positive electrode current collector. Specifically, the positive electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the positive electrode binder can be polyvinylidene fluoride.

[0056] In one embodiment of the present application, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (93-97.2): (0.5-2): (1-3). The appropriate ratio can improve the conductivity of the positive electrode sheet and the binding ability of the positive electrode sheet, which is beneficial to improving the electrochemical performance of the battery. Specifically, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder can be, but is not limited to, 93: 0.5: 1, 93.5: 0.8: 1.5, 94: 1: 1.8, 94.5: 1.2: 1.8, 95: 1.5: 2, 96: 1.8: 2.2, 96.5: 1.8: 2.5, 97: 2: 2.8 or 97.2: 2: 3, etc. In one embodiment of the present application, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder can be (93-96.5): (0.5-1.5): (1-2). In another embodiment of the present application, the mass ratio of the positive electrode active material, the positive electrode conductor and the positive electrode binder can be (95-97.2):(1-2):(2-3).

[0057] In one embodiment of the present application, combined with Figure 2 The negative electrode sheet 20 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on the surface of the negative electrode current collector 21. Specifically, the negative electrode current collector 21 may include, but is not limited to, at least one of copper, aluminum, nickel, and stainless steel. In one embodiment of the present application, the negative electrode current collector 21 may be a copper foil.

[0058] In one embodiment of the present application, the negative electrode active material layer 22 includes a negative electrode active material, and the negative electrode active material may include but is not limited to at least one of non-graphitized carbon, graphite, pyrolytic carbon, hard carbon, soft carbon, coke, and activated carbon. In one embodiment of the present application, the negative electrode active material may be hard carbon. In another embodiment of the present application, the negative electrode active material may be coke.

[0059] In one embodiment of the present application, the negative electrode active material layer 22 also includes a negative electrode conductive agent. The negative electrode conductive agent can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.

[0060] In one embodiment of the present application, the negative electrode active material layer 22 also includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the negative electrode current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide and styrene butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride.

[0061] In one embodiment of the present application, the negative electrode active material layer 22 further includes a negative electrode thickener, which can improve the binding ability between the negative electrode active material layer and the current collector and improve the uniformity of the negative electrode active material layer. Specifically, the negative electrode thickener can include but is not limited to at least one of sodium carboxymethyl cellulose and potassium carboxymethyl cellulose. In one embodiment of the present application, the negative electrode thickener can be sodium carboxymethyl cellulose.

[0062] In one embodiment of the present application, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode thickener is (92-96): (1-3): (2-5): (0.5-2). Specifically, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode thickener may be, but is not limited to, 92: 2: 4.5: 1.5, 93: 2: 2.5: 2, 93.5: 2.5: 3.5: 1.5, 94: 2: 3: 1, 94: 2: 3.5: 0.5, 95: 2.5: 2: 0.5 or 96: 0.5: 3: 0.5, etc. In one embodiment of the present application, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode thickener is (92-95): (1-2.5): (2-4.5): (0.5-1). In another embodiment of the present application, the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder and the negative electrode thickener is (93-96):(2-3):(3-5):(1-2).

[0063] In one embodiment of the present application, the battery further comprises a separator disposed between the positive electrode plate and the negative electrode plate. Specifically, the separator may be, but is not limited to, a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane or a separator paper.

[0064] The present application also provides an electrical device, which includes a battery provided by any of the above-mentioned embodiments. The electrical device provided by the present application has excellent comprehensive performance and strong market competitiveness. The electrical device of the present application may refer to a vehicle, an electronic device, an energy storage system, etc., and the above-mentioned electrochemical device may be arranged in the electrical device in the form of a single cell, a battery module, a battery pack, a capacitor, etc. In one embodiment of the present application, the battery can be used in a vehicle to improve the safety of the vehicle's electricity use. In another embodiment of the present application, the battery can also be used in electronic equipment to increase the high-temperature cycle stability of the electronic equipment battery and improve the battery life.

[0065] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0066] Example 1

[0067] In an argon atmosphere, 90 g of an organic solvent (30 g of propylene carbonate, 30 g of diethyl carbonate and 30 g of ethyl methyl carbonate) was mixed with 11 g of an electrolyte sodium salt (sodium hexafluorophosphate) until the electrolyte sodium salt was completely dissolved, and conventional additives (0.8 g of fluoroethylene carbonate, 0.4 g of vinyl carbonate, 0.8 g of vinyl sulfate, 0.8 g of 1,3-propane sultone, 0.5 g of methylene disulfonate) were added for the first mixing, and then 0.5 g of a dispersant (polyvinyl pyrrolidone) and 0.2 g of a wetting agent (sodium dodecylbenzene sulfonate) were added for the second mixing; 2.2 g of an electrolyte membrane stabilizer (Al2O3) was added for the third mixing, followed by high-speed shear dispersion for 30 minutes to form a stable emulsion electrolyte; wherein, based on the mass of the electrolyte, the mass percentage of the electrolyte membrane stabilizer was 2.05%, the mass percentage of the dispersant was 0.47%, and the mass percentage of the wetting agent was 0.19%.

[0068] Example 2

[0069] The difference from Example 1 is that the electrolyte membrane stabilizer is NaF.

[0070] Example 3

[0071] The difference from Example 1 is that the electrolyte membrane stabilizer is Na3PO4.

[0072] Example 4

[0073] The difference from Example 1 is that the electrolyte membrane stabilizer is NaAlO2.

[0074] Example 5

[0075] The difference from Example 1 is that the electrolyte membrane stabilizer is NaNO3.

[0076] Example 6

[0077] The difference from Example 1 is that the electrolyte membrane stabilizer is AlF3.

[0078] Example 7

[0079] The difference from Example 1 is that the electrolyte membrane stabilizer is Na2SO4.

[0080] Example 8

[0081] The difference from Example 1 is that the electrolyte membrane stabilizer is NaBr.

[0082] Example 9

[0083] The difference from Example 1 is that the electrolyte membrane stabilizer is Na2C2O4.

[0084] Example 10

[0085] The difference from Example 1 is that the mass percentage of the electrolyte membrane stabilizer in the electrolyte solution is 0.5%.

[0086] Embodiment 11

[0087] The difference from Example 1 is that the mass percentage of the electrolyte membrane stabilizer in the electrolyte is 5%.

[0088] Example 12

[0089] The difference from Example 1 is that the mass percentage of the dispersant in the electrolyte is 0.1%.

[0090] Embodiment 13

[0091] The difference from Example 1 is that the mass percentage of the dispersant in the electrolyte is 2%.

[0092] Embodiment 14

[0093] The difference from Example 1 is that the mass percentage of the wetting agent in the electrolyte is 0.05%.

[0094] Embodiment 15

[0095] The difference from Example 1 is that the mass percentage of the wetting agent in the electrolyte is 1%.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that no dispersant, wetting agent and electrolyte membrane stabilizer are added.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that no dispersant is added.

[0100] Comparative Example 3

[0101] The difference from Example 1 is that no wetting agent is added.

[0102] Comparative Example 4

[0103] The difference from Example 1 is that no electrolyte membrane stabilizer is added.

[0104] Performance Testing

[0105] The positive electrode active material (NaFe 0.33 Ni 0.33 Mn 0.33 O2, sodium nickel iron manganese oxide), a positive electrode binder (polyvinylidene fluoride) and a positive electrode conductor (carbon black) are mixed in a mass ratio of 96.5:1.5:2, and a solvent (N-methylpyrrolidone) is added to mix to obtain a positive electrode slurry; the positive electrode slurry is coated on a double-sided current collector (aluminum foil), dried, and rolled to obtain a positive electrode sheet;

[0106] The negative electrode active material (hard carbon), the negative electrode conductive agent (carbon black), the negative electrode thickener (sodium carboxymethyl cellulose) and the negative electrode binder (styrene-butadiene rubber) are mixed in a mass ratio of 94:2:2:3, and water is added to prepare the negative electrode slurry; the negative electrode slurry is coated on a double-sided current collector (copper foil or aluminum foil), dried, and rolled to obtain a negative electrode sheet;

[0107] After the positive electrode sheet and the negative electrode sheet are die-cut, assembled and baked, the electrolyte prepared in the above-mentioned Examples 1-15 and Comparative Examples 1-4 is injected, and the battery is prepared by performing formation charging, aging and capacity separation.

[0108] The batteries prepared in the above-mentioned Examples 1-15 and Comparative Examples 1-4 were subjected to a charge and discharge performance test. The test process was as follows: charging to 4.0V at 0.1C constant current at room temperature, performing the first formation charge, then aging at 45°C, exhausting and sealing, and then discharging to 1.5V at 0.2C constant current; recording the discharge capacity and charge capacity of the battery, and the first coulomb efficiency (%) = discharge capacity / charge capacity × 100%. The test results are shown in Table 1.

[0109] The batteries prepared in the above-mentioned Examples 1-15 and Comparative Examples 1-4 were subjected to a high-temperature cycle performance test. The test process was as follows: at 45°C, the batteries were charged to 4.0V at a constant current of 1C, then charged to 4.0V at 0.2C, left for 10 minutes, then discharged to 1.5V at a constant current of 1C, and then discharged to 1.5V at a constant current of 0.2C. The above-mentioned charge and discharge method was used for a 45°C cycle test. The first-cycle discharge capacity was taken as 100% capacity, and the capacity retention rate and gas production were recorded after 500 cycles. A thickness expansion rate of less than 3% was judged as slight gas production, a thickness expansion rate of 3%-10% was judged as moderate gas production, and a thickness expansion rate greater than 10% was judged as severe gas production. The test results are shown in Table 1.

[0110] Table 1 Performance test results

[0111]

[0112] It can be seen from Examples 1-15 and Comparative Examples 1-4 that the electrolyte provided in the present application can effectively inhibit the dissolution of the electrolyte membrane, inhibit the occurrence of gas production, and improve the battery's initial efficiency, capacity retention rate, and high-temperature cycle stability. It can be seen from Example 1 and Examples 2-15 that a suitable electrolyte membrane stabilizer, an appropriate amount of electrolyte membrane stabilizer, a dispersant, and a wetting agent can promote the uniform dispersion of the electrolyte, inhibit the dissolution of the electrolyte membrane, improve the high-temperature cycle stability of the battery, and enhance the battery's initial efficiency and capacity. It can be seen from Example 1 and Comparative Examples 1-4 that the electrolyte membrane stabilizer is uniformly dispersed in the electrolyte under the joint action of the dispersant and the wetting agent, can be deposited on the surface of the electrode plate, and can be slowly released during the use of the battery to inhibit the dissolution of components in the electrolyte membrane and improve the battery's capacity and high-temperature cycle stability.

[0113] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes electrolyte sodium salt, additives and organic solvent; the additives include dispersant, wetting agent and electrolyte membrane stabilizer, and the electrolyte membrane stabilizer includes at least one of alkali metal halide, sodium compound and aluminum compound.

2. The electrolyte according to claim 1, characterized in that The alkali metal halide includes at least one of NaF, NaCl, NaBr, KF, KCl and KBr; the sodium compound includes Na3PO4, Na4P2O7, (NaPO3)2, NaPO3, Na5P3O 10 , NaAlO2, Na2SO4, NaAlF4, Na2C2O4, NaNO3 and NaNO2; the aluminum compound includes at least one of Al2O3, Al(OH)3 and AlF3.

3. The electrolyte according to claim 2, characterized in that The electrolyte membrane stabilizer includes at least one of NaF, KF, NaBr, Na2C2O4, Na3PO4, NaAlO2, Al2O3, AlF3, NaNO3 and Na2SO4.

4. The electrolyte according to any one of claims 2 or 3, characterized in that The electrolyte membrane stabilizer includes at least one of Al2O3, NaNO3, AlF3 and Na2C2O4.

5. The electrolyte according to any one of claims 1 to 4, characterized in that The Dv50 particle size of the electrolyte membrane stabilizer is less than or equal to 200 nm.

6. The electrolyte according to claim 1, characterized in that Based on the mass of the electrolyte, the mass percentage of the electrolyte membrane stabilizer is 0.5%-5%; the mass percentage of the dispersant is 0.1%-2%; the mass percentage of the wetting agent is 0.05%-1%; the mass percentage of the electrolyte sodium salt is 7.43%-14.9%; and the mass percentage of the organic solvent is 74.32%-91.4%.

7. The electrolyte according to any one of claims 1 to 6, characterized in that The dispersant comprises at least one of polyvinyl pyrrolidone, polyethylene glycol and sodium polystyrene sulfonate; and / or, the wetting agent comprises at least one of diallyldimethylammonium chloride, sodium dodecylbenzenesulfonate and hexadecyltrimethylammonium bromide; and / or, the electrolyte sodium salt comprises at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisoxalatoborate, sodium difluorophosphate, sodium difluorooxalatoborate, sodium difluorobisoxalatophosphate and sodium bisfluorosulfonyl imide; And / or, the organic solvent includes at least one selected from cyclic carbonate, linear carbonate, propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, ethyl propionate and methyl butyrate.

8. The electrolyte according to claim 1, characterized in that The additives also include conventional additives, which include at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, propenyl-1,3-sultone, methylene disulfonate, vinyl sulfate, trimethylsilyl phosphate, trimethylsilyl phosphite, trimethylsilyl borate, succinonitrile, 1,3,6-hexanetrinitrile and adiponitrile.

9. The electrolyte according to claim 8, characterized in that The mass percentage of the conventional additives is 0.093%-4.97%.

10. The electrolyte according to claim 1, characterized in that The electrolyte is in a colored emulsion state.

11. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte arranged between the positive electrode sheet and the negative electrode sheet, and the electrolyte comprises the electrolyte according to any one of claims 1 to 10.

12. An electrical device, characterized in that: The electrical device comprises the battery according to claim 11.